Effect of induced crystallization in rare-earth doped lithium borate glass. (July 2016) - Steudel, Franziska; Rimbach, A. Charlotte; Loos, Sebastian; Ahrens, Bernd; Schweizer, Stefan
Abstract: Rare-earth doped borate glasses and glass ceramics are investigated for their potential as photon converters. Thermal processing of the as-made glass results in the formation of nanocrystals therein. For optical activation, the glasses are doped with Eu 3+ and Tb 3+, both enabling an intense emission under ultraviolet excitation. Differential scanning calorimetry and X-ray diffraction are applied to analyze the crystallization behavior. Compared to the undoped glass, the glass transition temperature as well as the crystallization temperature are increased with Eu 3+ doping. Upon thermal processing of the as-made glasses, the transmittance is significantly reduced. Preliminary photoluminescence quantum efficiency measurements yield lower values for the glass ceramics. Highlights: Thermally-induced formation of nanocrystals in rare-earth doped Li borate glass. Higher crystallization tendency in undoped compared to the rare-earth doped glass. Increase of glass transition and crystallization temperatures with Eu 3+ doping. Decrease of transmittance and luminescence quantum efficiency with crystallization.